Using 24-h Heart Rate Variability to Investigate the Sleep Quality and Depression Symptoms of Medical Students - Guo, Xiansheng; Su, Tiehong; Xiao, Haoran; Xiao, Rong; Xiao, Zhongju (Frontiers in Psychiatry, 2022)
There have been numerous studies on the relationship between sleep and depression, as well as the relationship between sleep and depression, and heart rate variability, respectively. Even so, few studies have combined 24-hour heart rate variability analysis to study sleep quality and depressive symptoms. The purpose of current study was to investigate the relationship between depressive symptoms of sleep quality and 24-hour heart rate variability of medical students, and its internal mechanism. The particiants were all students at a medical university in Guangdong province, China. A total of 74 college students participated. They were asked to complete a questionnaire that included the Pittsburgh Sleep Quality Index (PSQI), the Beck Depression Inventory-II (BDI-II), the Positive and Negative Affect Schedule (PANAS), and 24-hour ECG monitoring. The results showed that 41.7% of the medical students had poor sleep quality, with higher levels of depressive symptoms and more negative emotions, and there was no difference in 24-hour HRV indices between the low PSQI group and the high one. Correlation analysis showed that there was a significant relationship between sleep quality and depressive symptoms (r = 0.617), but the relationship between 24-hour HRV indices and PSQI global scores, BDI scores were not significant. However, the correlation analysis of PSQI components and 24-hour HRV showed that sleep disturbance was significantly negatively correlated with SDNN and LF in waking period (r = -0.285, -0.235), and with SDNN in sleeping period (r = -0.317). In general, the sleep disturbance in PSQI components can sensitively reflect the relationship between sleep quality and 24-hour HRV of medical students. Individuals with higher sleep disturance may have lower SDNN during awake period and bedtime period, and lower LF in awake period. 24-hour HRV has certain application value in clinical sleep quality monitoring, and its sensitivity and specificity in clinical application and daily life are still worth further investigation.